An effective and facile approach for the determination of bioactive components of Rheum ribes in the Kurdish state of Iraq and Siirt region in Turkey - Tegin İbrahim; Fattah Bakhtiyar Mahmood Fattah; Fidan Mehmet; Acar Orhan; Yabalak Erdal (Journal of the Serbian Chemical Society)
Developing a streamlined and accessible method for identifying the bioactive components of Rheum ribes (rhubarb) holds significant promise in unlocking its therapeutic potential and advancing research in natural medicine. In this study, the bioactive components of rhubarb such as total phenolics and flavonoids as well as the antioxidant activity of its methanolic extract were determined. Total phenolic content was between 84.02 and 387.53 mg/L gallic acid equivalent (GAE) in extracts. Total flavonoid contents determined by the aluminium chloride colorimetric method ranged from 69.98 to 935.75 mg L-1 of routine equivalents (RE) in the extracts. The antioxidant activities were determined using ferric reducing the antioxidant potential (FRAP) and 1,1-diphenyl- -2-picrylhydrazyl (DPPH) methods. In the FRAP assay, the highest antioxidant activity (IC50) was found as 25.18±0.04 mg L-1 extract. In the DPPH method, the maximum percentage inhibition was found as 88.11 %. Iron chelating activities of the samples were above 70 %. The chemical compound contents of the extracts were determined by LC–MS/MS. In this step, a total of 25 phenolic and flavonoid compounds in extracts were analysed qualitatively and quantitatively. Malic acid (15.72±0.53 mg kg-1) and rutin (76.93±0.03 mg kg-1) in the extract were identified as the major phytochemicals compounds. The results of the study confirm that rhubarb have potential biological activities and can be introduced as an important sources of natural antioxidants.